The Influence of Supervision and Employee Competence on the Performance of the Safety Development Sector of the South Tangerang City Transportation Office - Anggario Gilang Pratama (Jurnal Syntax Admiration, 2023)
This research aims to analyze the influence of supervision and employee competency together on employee performance in the Safety Development Sector of the South Tangerang City Transportation Service. The hypotheses tested are: (1) There is an influence of supervision on employee performance in the Safety Development Sector of the South Tangerang City Transportation Service. (2) There is an influence of employee competency on employee performance in the Safety Development Sector of the South Tangerang City Transportation Service. (3) There is a joint influence of employee supervision and competence on employee performance in the Safety Development Sector of the South Tangerang City Transportation Service. This research includes explanatory research, associative research and quantitative analysis with a survey approach. In this research, the sampling technique used is Simple Random Sampling, where this method is used if members of the population are considered homogeneous because the sample is representative or the sample is taken randomly. The sample in this study consisted of 72 respondents. The data analysis technique uses the correlation coefficient analysis method, coefficient of determination analysis, partial significance test (t test), simultaneous significance test (F test), and simple and multiple regression analysis. From the research results, the following conclusions were obtained: First, supervision has a strong and significant influence on employee performance with a correlation coefficient value of 0.722 and a coefficient of determination (r²) value of 0.521, meaning that the supervision variable contributes 52.1% to the employee performance variable.